Num lugar, projectar um lugar. A casa do meu irmão. - Jorge Miguel Azevedo Dias (2015)
In a Place, Project a Place: My Brother's House centers in the study of the dialogue between the architectural creation and the architect, considering several objectives and steps in the project of a House. The intention is to study the architect's influences in architecture and in his creative process, whether they're theoretical or practical. The architect doesn't always have the conscience of what motivates the Project, neither of the influences that he's submitted to. That's why, sometimes, the project results in bad solutions, as part of the whole process. Therefore, the project of a house happens as a motive to study this dialectic, where the "house" is the creation that concentrates, in a minimalistic view, the simplicity of the shelter and the complexity of contemporaneity. With the interrelation between the observer's imageries and the observed space, we investigate types of intern and extern dwelling, over the XX century, in Portugal and in the world. We arrive to the conclusion that dwelling can have many forms, but just the forms don't mean anything, if not fused with space. We search for the correlation between the house and the place and between the house and the people. To relate intimately with the place, we have to experience the spaces that define the place, and to relate with the people, we have to serve their needs. Therefore, takes into account the client, his job, and his life style, to create a righteous program. We perceive the morphologic tradition of the place and the modern examples of architecture in the region, to connect to the way of dwelling in the place, where it's going to construct. For last, we study the things that can intervene in the creative process and the steps of it, in order to define the relations and references that were established. It's a search for the insertion of a new body, in a natural, solid, strong and secure connection with the architect, with the clients and with the place to live.